1999
DOI: 10.1038/sj.leu.2401440
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant hematopoiesis in mice with inactivation of the gene encoding SOCS-1

Abstract: Mice with homozygous inactivation of the gene encoding the suppressor of cytokine signaling-1 (SOCS-1) protein die within 21 days of birth with low body weight, fatty degeneration and necrosis of the liver, infiltration of the lung, pancreas, heart and skin by macrophages and granulocytes and a profound depletion of T-and B-lymphocytes. In the present study, SOCS-1 −/− mice were found to have a moderate neutrophilia, and reduced platelet and hematocrit levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 18 publications
4
57
0
Order By: Relevance
“…STAT1 activation was also prolonged in SOCS-1 Ϫ/Ϫ hepatocytes treated with IFN-␥ in vitro. Furthermore, in some cells of the hematopoietic lineage, SOCS-1 deficiency has been shown to result in hypersensitivity to IFN-␥ (39,44). Consistent with studies in other cell types, we found that overexpression of SOCS-1 suppressed responses to IFN-␥ in NIT-1 insulinoma cells, such as IFN-␥-induced STAT1 activation, class I MHC upregulation, and cell death.…”
Section: Discussionsupporting
confidence: 90%
“…STAT1 activation was also prolonged in SOCS-1 Ϫ/Ϫ hepatocytes treated with IFN-␥ in vitro. Furthermore, in some cells of the hematopoietic lineage, SOCS-1 deficiency has been shown to result in hypersensitivity to IFN-␥ (39,44). Consistent with studies in other cell types, we found that overexpression of SOCS-1 suppressed responses to IFN-␥ in NIT-1 insulinoma cells, such as IFN-␥-induced STAT1 activation, class I MHC upregulation, and cell death.…”
Section: Discussionsupporting
confidence: 90%
“…Mice lacking SOCS-1 display erythroid defects, including a subnormal hematocrit and an accumulation of immature red blood cells Metcalf et al, 1999). Data presented here indicate that the erythroid abnormalities in SOCS-1À/À mice may be due, in part, to the increased sensitivity of red cell progenitors to Epo (Figure 7).…”
Section: Discussionmentioning
confidence: 65%
“…They are either induced by Epo (Yoshimura et al, 1995;Starr et al, 1997;Pircher et al, 2001) or expressed in fetal liver (Starr et al, 1997;Marine et al, 1999). While CIS À/À mice have no detectable phenotype (Marine et al, 1999), SOCS-1À/À mice suffer from mild anemia and an excess of nucleated erythroid cells in the spleen Metcalf et al, 1999). It has been reported that SOCS-3 is essential for fetal liver erythropoiesis (Marine et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…SOCS2 and SOCS3 knockout mice are lethal, whereas SOCS2 knockout mice are 30% larger than their wild-type counterparts. [182][183][184][185] There are other mechanisms to downregulate Jak/STAT signaling. Protein phosphatases, including CD45 and protein tyrosine phosphatase-e C (PTPeC), are also implicated in the negative regulation of Jak/STAT signaling.…”
Section: Overview Of Jak/stat Pathwaymentioning
confidence: 99%